Presenting Symptoms and Disease Severity in Multiple Sclerosis Patients - Jason Ledesma; Padma Priya Puttagunta; Shayan Torabi; Kristen Berube; Eric Tamrazian; Diamond Garcia; Bijal Kirit Mehta (MDPI AG, 2021)
Introduction: The study aims to determine an association between presenting symptoms in multiple sclerosis and measures of disease severity, including the expanded disability status score (EDSS) and MRI based lesion volumes. Methods: Data was collected as part of a larger 3 year MS study, from 2014 to 2017, to compare Vitamin A levels and MS progression. All data was collected from a single clinical site. Demographic data as well as date of diagnosis and use of disease modifying therapies. Patients not able to obtain MRIs or lab tests and histories of vitamin abnormalities were excluded from the study. 29 patients met inclusion criteria. We chose presenting symptoms of vision, balance, sensory function, and motor function as these represented the most common manifestations of the disease and mirror the domains of the EDSS, which is the most commonly used scale for MS disease severity. We also included neuroimaging based lesion volume as another objective measure for comparison. Results: Although duration of disease was different between comparator groups, no significant difference was found between them when EDSS and lesion volumes were compared. There was a difference in lesion volumes when comparing those patients that had presenting symptoms of visual changes or balance symptoms with those presenting with sensory changes. Conclusions: This study supports the notion that presenting symptoms are not associated with EDSS independent disease duration. It also verifies that severity of disease is not associated with lesion volumes. However, sensory symptoms as a presenting symptom was associated with less lesion volumes in our study.